2020
DOI: 10.1111/jfpp.15055
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene loaded polylactic acid (PLA) and PLA/copolymer electrospun nanofibers, synthesis, characterization, and control release

Abstract: The effect of different copolymers on the morphological and encapsulating properties of polylactic acid (PLA) nano(micro)fiber and potential of the fibers for controlling lycopene release rate were studied. The lycopene loaded fibers developed from PLA and different copolymers including polyethylene oxide (PEO), polyacrylic acid, and cellulose acetate (CA) using electrospinning. Diameters and morphology of fabricated fibers are assessed using scanning electron microscopy. Encapsulation of the lycopene in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 59 publications
0
5
0
1
Order By: Relevance
“…It also could be a promising candidate for postoperative chemotherapy. Hajikhani et al reported the encapsulating properties of nanofibers derived from electrospinning of copolymers of PAA, polylactic acid, cellulose acetate, and polyethylene oxide for controlled release lycopene [ 230 ]. Khajeh et al reported using biocompatible nanofibers derived from electrospinning of PAA, poloxamer, and polyurethane for wound dressing.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…It also could be a promising candidate for postoperative chemotherapy. Hajikhani et al reported the encapsulating properties of nanofibers derived from electrospinning of copolymers of PAA, polylactic acid, cellulose acetate, and polyethylene oxide for controlled release lycopene [ 230 ]. Khajeh et al reported using biocompatible nanofibers derived from electrospinning of PAA, poloxamer, and polyurethane for wound dressing.…”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…chitosan [152][153][154][155][156], collagen [157][158][159][160], SF [161][162][163][164], gelatin [165][166][167][168][169][170]) and synthetic polymers (e.g. PGA [171][172][173], poly lactic acid (PLA) [174][175][176][177][178][179], PLGA [180][181][182][183][184][185][186][187][188], poly vinylpyrrolidone (PVP) [77,[189][190][191][192][193][194], PCL [195][196][197][198][199][200]<...…”
Section: Electrospinningunclassified
“…Lycopene could be encapsulated in a variety of materials, such as hydrogels, 8 films, 9 nanoparticles, 10 nanoliposomes, 11 and electrospun fibers. 12 In particular, the encapsulation of lycopene into electrospun fibers can offer great benefits including versatile encapsulation routes, ease of fabrication, enhanced stability, controlled release, and combination therapies. In this regard, due to the poor water solubility of lycopene, organic solvents, acidic solutions, or emulsion routes are commonly used for its encapsulation into electrospun fibers or electrosprayed beads.…”
Section: Introductionmentioning
confidence: 99%
“…Lycopene has also been encapsulated in polylactic acid (PLA) and PLA-based electrospun fibers. 12 Differential scanning calorimetry was used to validate the change in the thermal stability of the encapsulated lycopene. The addition of cellulose acetate affected the fiber shape and reduced the lycopene release rate compared to other polymers such as poly(acrylic acid) and poly(ethylene oxide).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation